First record of the beetle family Throscidae (Insecta: Coleoptera), a new species of Aulonothroscus Horn, and new species records to the fauna of Peru - Johnson, Paul J. (2016)
The beetle family Throscidae is documented from Peru for the first time, based on specimens collected in the regions of Cajamarca, Junín, Loreto and Madre de Dios. Aulonothroscus tambopata new species is described from Madre de Dios. Also, three additional species of Aulonothroscus are reported from Peru for the first time – A. alvarengai Cobos new country record, A. freudi Cobos new country record, and A. oculatissimus Cobos new country record. A key separating these four species is given. This report is part of the “Beetles of Peru” project.